Mechanism of hemorrhagic stroke in the old patiens with COVID-19 (Ictus, 2021)
Letter to de editor received for volume 2 number 3 of ICTUS, official organ of the Mexican Association of Cerebral Vascular Disease.
Keywords: Hemorrhagic stroke; COVID-19; SARS-CoV2; Old patient